PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PENGGUNA NOTEBOOK ACER PADA PT. GENIUS ALVA MAKASSAR - Muhammad Amir (AkMen JURNAL ILMIAH, 2018)
This study aims to determine the effect of product quality on consumer satisfaction of Acer Notebook users at PT. Genius Alva Makassar. The types of data used are qualitative and quantitative data, data sources used, namely primary data and secondary data. The collected data were analyzed descriptively, ie the data obtained in the field were processed in such a way as to provide a systematic understanding, then statistical calculations were carried out by simple regression analysis, correlation coefficient, determination coefficient (r ^ 2) and t-test. From the calculation results obtained a value of y = 17.51 ​​+ 0.63 x, while the correlation coefficient (r) is 0.527 and the coefficient of determination (r ^ 2) is 27.77%, the result of the t-test calculation where t-count> t-table is 3.522 > 2,034, this states that there is a true influence of product quality on consumer satisfaction on Acer Notebook users at PT. Genius Alva Makassar.